An Event-B-Based Approach to Model and Verify Behaviors for Component-Based Applications. (15th September 2021) - Mammar, Amel; Hamel, Lazhar; Graiet, Mohamed
Abstract: Many disciplines have adopted component-based principles to avail themselves of the many advantages they bring, especially component reusability. In a short time, the component-based architecture became a renown branch in the IT world and the center of interest of many researchers. Much work has been conducted in this context for the verification of component-based applications (CBAs). However, the main focus has been on the structural aspect of such compositions, while the behavioral aspect has seldom been dealt with. In this paper, our goal is to close this gap and propose a formal approach to verify the behavioral correctness of CBAs. We first define a set of requirements to be satisfied by the structure and the behavior of a CBA, represented by a set of interactions that may occur between their components. Then, we build a formal Event-B model to represent these requirements in a rigorous and non-ambiguous way. The use of the Event-B refinement technique allows us to master the complexity of CBAs by introducing their elements in an incremental manner. The correctness of the development is ensured by establishing a set of proof obligations, under the Rodin platform, and also by animating it with the ProB animator/model checker. The approach is illustrated by a running example.